Sonoelectrochemical intercalation and exfoliation for the preparation of defective graphene sheets and their application as nonenzymatic H2O2 sensors and oxygen reduction catalysts. Issue 28 (25th February 2015) - Chen, Chin-Wei; Liu, Zhe-Tin; Zhang, Yu-Zhen; Ye, Jyun-Sian; Lee, Chien-Liang
Abstract : A sonoelectrochemical synthetic method is reported for rapidly preparing and dispersing reduced graphene nanosheets (RGNSECM ) stabilized in an aqueous electrolyte. Abstract : A sonoelectrochemical synthetic method is reported for rapidly preparing and dispersing reduced graphene nanosheets (RGNSECM ) stabilized in an aqueous electrolyte. The X-ray photoelectron and Raman results demonstrate that the defects on RGNSECM are predominantly physical and not similar to the chemical defects on reduced graphene nanosheets (RGNCM ) synthesized via chemical reduction of graphene oxide nanosheets based on the Hummer's method. The in-plane crystallite size ( L a ) of RGNSECM is 26.8 nm, larger than the 18.2 nm of RGNCM . The RGNs prepared using the sonoelectrochemical method (RGNSECM ) were successfully applied as nonenzymatic H2 O2 sensors and alkaline oxygen reduction reaction (ORR) catalysts. Using electrochemical analysis, a fair comparison of the performances of RGNSECM and RGNCM as H2 O2 sensors and ORR catalysts has been performed.